The influence of print exposure on the body-object interaction effect in visual word recognition - Hansen, Dana; Siakaluk, Paul D.; Pexman, Penny M. (Frontiers in Human Neuroscience, 2012)
We examined the influence of print exposure on the body-object interaction (BOI) effect in visual word recognition. High print exposure readers and low print exposure readers either made semantic categorizations (“Is the word easily imageable?”; Experiment 1) or phonological lexical decisions (“Does the item sound like a real English word?”; Experiment 2). The results from Experiment 1 showed that there was a larger facilitatory BOI effect for the low print exposure readers than for the high print exposure readers in semantic categorization, though an effect was observed for both print exposure groups. However, the results from Experiment 2 showed that a facilitatory BOI effect was observed only for the high print exposure readers in phonological lexical decision. The results of the present study suggest that print exposure does influence the BOI effect, and that this influence varies as a function of task demands.